1986
DOI: 10.1016/0033-5894(86)90004-9
|View full text |Cite
|
Sign up to set email alerts
|

14C and Th/U Dating of Pleistocene and Holocene Stromatolites from East African Paleolakes

Abstract: During recent humid episodes, stromatolites were built along paleolake margins, some 60 m above the modern water level of Lakes Natron and Magadi (southern Gregory Rift Valley). Three generations of stromatolites are observed, the more recent ones frequently covering pebbles and boulders eroded from the older ones. The youngest one yielded 14C ages ranging from approximately 12,000 to 10,000 yr B.P. Their δ13C values (≥2.6%) suggest isotopic equilibrium between the paleolake total inorganic dissolved carbon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…For the Lake Natron-Magadi Basin north of Lake Manyara ages for stromatolites and related shorelines (ca. 240,000 y BP, 135,000 ± 10,000 y BP and from 12,000 to 10,000 y BP) have been found to differ from the ages of stromatolites of the Lake Manyara Basin, but agree with the ages of the other lake systems mentioned before, and the ages of the drilling cores of Lake Manyara [3,48]. The comparison of stromatolite ages in East African lake systems may involve a methodological problem, because the encrusting benthic microbial communities react very sensitively to changes in water chemistry and hydrological conditions.…”
Section: Study Area and Paleolake Evidencesupporting
confidence: 84%
See 1 more Smart Citation
“…For the Lake Natron-Magadi Basin north of Lake Manyara ages for stromatolites and related shorelines (ca. 240,000 y BP, 135,000 ± 10,000 y BP and from 12,000 to 10,000 y BP) have been found to differ from the ages of stromatolites of the Lake Manyara Basin, but agree with the ages of the other lake systems mentioned before, and the ages of the drilling cores of Lake Manyara [3,48]. The comparison of stromatolite ages in East African lake systems may involve a methodological problem, because the encrusting benthic microbial communities react very sensitively to changes in water chemistry and hydrological conditions.…”
Section: Study Area and Paleolake Evidencesupporting
confidence: 84%
“…In an analysis of stromatolites from the northwestern area of today's lake extent close to the town of Mto Wa Mbu ( Figure 1) [18], late Pleistocene and Holocene stromatolites collected on a distinct level of 20 m above today's lake level were dated by 14 C and Th/U series. Results showed humid periods with high lake levels for 22,000 y BP (increased water residence time, nutrient enrichment), 27,000 to 23,000 y BP (stable hydrological conditions with diluted fresh water), 35,000 to 32,000 y BP, 90,000 y BP, and an uncertain age of about 140,000 y BP [18,48]. Other research groups dated the humid period between 27,500 and 26,000 y BP, and an even younger high stand between 12,700 to 10,000 y BP by diatom analysis of two drilling cores from Lake Manyara [15,16].…”
Section: Study Area and Paleolake Evidencementioning
confidence: 99%
“…Stromatolites, which can be found on the shorelines and within drilling cores of the lake, have been radiometrically dated [Holdship, 1976;Barker, 1990]. Humid periods with high lake levels could be identified for the following periods: 12,700 to 10,000 y BP, 22,000 y BP, 27,500 to 26,000 y BP, 27,000 to 23,000 y BP, 35,000 to 32,000 y BP, 90,000 y BP, and an uncertain age of about 140,000 y BP [Hillaire-Marcel et al, 1986;Casanova and Hillaire-Marcel, 1992]. …”
Section: Study Area and Geo-archaeological Contextmentioning
confidence: 99%
“…In the East African region, several studies have been conducted to document variability in palaeo-precipitation and climate variability using various indicators such as diatoms, mineral magnetic, pollen, stable isotopes and lake levels (Hillaire-Marcel et al 1986, Hillaire-Marcel and Cassanova, 1987, Johnson et al 1996& 2000, Olago et al 2000, Stager et al 1997, Karlén et al 1999, Gasse, 2000, Talbot and Laerdal 2000, Thompson et al 2002. Some of these studies have indicated that precipitation at the end of the last glacial period was low, and lake levels were at their lowest level, with shallower lakes like Lake Victoria being completely dry (Johnson et al 1996, Stager et al 1997, Talbot and Laerdal 2000.…”
Section: Introductionmentioning
confidence: 99%
“…This dry phase was later followed by an increase in precipitation to a maximum level during the early Holocene that culminated at about 5 ka (Hillaire-Marcel and Cassanova 1987, Stager and Mayewski 1997, Stager et al 1997, Gasse 2000. Although there is a significant amount of information on the climatic condition in the East African region, documentation of climatic changes in northern Tanzania is scanty and available information has been obtained using stromatolites (Hillaire-Marcel et al 1986, Hillaire-Marcel andCassanova 1987) and diatoms (Roberts et al 1993). Furthermore, there is a great potential of using stable isotopes in paleoclimatic studies, but it is evident that only a few studies have used stable isotopes of OC and nitrogen to document climatic changes in Tanzania (Johnson et al 2000, Talbot andLaerdal 2000).…”
Section: Introductionmentioning
confidence: 99%